Elementary Teacher Leadership of Pioneer Teacher Program Alumnae in Yogyakarta City - Brilatin, Ares; Wibowo, Setiawan Edi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
This research examines the leadership of Pioneer Teacher Program (Guru Penggerak) graduates at the primary school level in Yogyakarta City. It is a descriptive qualitative research. This research applies educational sociology approach, particularly the role of teachers. Data was collected from interviews and literature reviews. The data analysis is based on the theory of teachers as leaders by Frank Crowther (1997). The results of this research: first, GP graduates of the Pioneer Teacher Program have successfully improved their quality and professionalism in the leadership. This improvement is manifested in proactive involvement in various leadership activities. Second, the Self-Efficacy of Prioneer Teacher is not prevalent. Some GP members face personal and casuistic issues, where their lack of confidence emerges when faced with strategic leadership positions, such as being a school principal. The research findings controvert the common narrative that the Pioneer Teacher Program produces successful teachers without any obstacles. These findings serve as a recommendation for the future Pioneer Taecher Program to emphasize and pay more attention to the self-confidence of its graduates in strategic leadership positions within their respective institutions.